Pemberdayaan Petani Desa Borehbangle Melalui Pelatihan Pembuatan Pupuk Cair Organik Jenis NPK dan Urea - Zulfatun Anisah; M. Mun’im; Aslikhatun Khoiriyah; Anzilly Ifadatun Ummah; Ilvi Mawaddah; Riska Nur Aini; Nurul Lathifatul Fithriya; Zakiyatun Nabila; Putri Syafaatun; Novi Arilia Safitri; Iva Nur Zakiya; Khoirun Nisa; Yumi Kholifah; Narwikah Narwikah; Nur Hasanah; Yayuk Sri Kasiani; Sholihah Roekhana (Universitas Muhammadiyah Manado, 2024)
The majority of the Borehbangle village community works as farmers, and their main need in supporting agriculture is fertilizer. However, the farmers face challenges in obtaining subsidized fertilizers from the government, causing concern. Additionally, the farmers lack the skills to process organic fertilizer into liquid fertilizer that they can utilize. Therefore, the objective of this community service is to assist farmers in improving their skills in processing organic fertilizer into liquid fertilizer that can be used in agricultural activities. The partners in this service project are the farmers of Borehbangle village and the Agricultural Service Agency (BPP) of Merakurak. The method used is Participatory Action Research (PAR), with approaches that include mapping, transect walks, field notes, seasonal calendars, Venn diagrams, flow charts, as well as historical tracing and problem trees. The community service team collaborated with BPP Merakurak to conduct training on producing organic liquid fertilizers, specifically NPK and urea. The results of this project show that the farmers actively participated in the socialization and direct training on producing organic liquid fertilizers. Moreover, they are now able to apply this knowledge independently at their homes. This training had a significant impact on improving the farmers' self-reliance in addressing fertilizer issues, ultimately supporting the sustainability of agriculture in Borehbangle village.